Atomic Spectroscopy Analysis of Heavy Metals in Plants: Atomic Spectroscopy Analysis of Heavy Metals in Plants - Mukhopadhyay, G (International Journal of Pharmaceutical & Biological Archive, 2018)
This study depicts a profile of existence of heavy metals (Cu, Cr, Cd, Hg, As, and Pb) in some important medicinal plants such as Hibiscus rosa-sinensis, Eclipta alba, and Solanum nigrum using atomic absorption spectroscopy. H. rosa-sinensis, E. alba, and S. nigrum these are indigenous plants having tremendous medicinal properties. Extracts of these plants are already reported to have many pharmacological activities. The purpose of this study is to determine heavy metal contents in these medicinal plants. The findings of this study were compared with prescribed limits of these metals in the WHO guidelines, and the content of all these heavy metals was found to be within safe limits. These findings indicate that the extract of H. rosa-sinensis, E. alba, and S. nigrum is safe from the point of view of heavy metal toxicity.